Issues and solutions toward zinc anode in aqueous zinc‐ion batteries: A mini review - Chunlin Xie; Yihu Li; Qi Wang; Dan Sun; Yougen Tang; Haiyan Wang (Carbon Energy, 2020)
Abstract Aqueous zinc‐ion batteries (ZIBs) have been intensively investigated as potential energy storage devices on account of their low cost, environmental benignity, and intrinsically safe merits. With the exploitation of high‐performance cathode materials, electrolyte systems, and in‐depth mechanism investigation, the electrochemical performances of ZIBs have been greatly enhanced. However, there are still some challenges that need to be overcome before its commercialization. Among them, the obstinate dendrites, corrosion, and hydrogen evolution reaction (HER) on Zn anodes are critical issues that severely limit the practical applications of ZIBs. To address these issues, various strategies have been proposed, and tremendous progress has been achieved in the past few years. In this article, we analyze the origins and effects of the dendrites, corrosion, and HER on Zn anodes in neutral and mildly acid aqueous solutions at first. And then, a scientific understanding of the fundamental design principles and strategies to suppress these problems are emphasized. Apart from these, this article also puts forward some requirements for the practical applications of Zn anodes as well as several cost‐effective‐modifying strategies. Finally, perspectives on the future development of Zn anodes in aqueous solutions are also briefly anticipated. This article provides pertinent insights into the challenges on anodes for the development of high‐performance ZIBs, which will greatly contribute to their practical applications.